The Expanding Role of Quantitative Pupillometry in the Evaluation and Management of Traumatic Brain Injury - Boulter, Jason H.; Shields, Margaret M.; Meister, Melissa R.; Murtha, Gregory; Curry, Brian P.; Dengler, Bradley A. (Frontiers in Neurology, 2021)
Traumatic brain injury is a rapidly increasing source of morbidity and mortality across the world. As such, the evaluation and management of traumatic brain injuries ranging from mild to severe are under active investigation. Over the last two decades, quantitative pupillometry has been increasingly found to be useful in both the immediate evaluation and ongoing management of traumatic brain injured patients. Given these findings and the portability and ease of use of modern pupillometers, further adoption and deployment of quantitative pupillometers into the preclinical and hospital settings of both resource rich and medically austere environments.